Antibacterial Functionalization of Silk Fabrics following in Situ Coloring with Diazo Salts. Issue 11 (2nd November 2021) - Wei, Ye; Yu, Xuejie; Wang, Ping; Yu, Yuanyuan; Yuan, Jiugang; Wang, Qiang; Fan, Xuerong
ABSTRACT: Bombyx mori silk fabrics are generally dyed with acid dyestuffs at high temperature, and it has the disadvantages of overmuch energy-consumption. In the present work, in situ coloring of silk fabric was performed using diazo salts of aromatic amines, aiming at achieving high color fastness with less energy consumption. Subsequently, graft copolymerization of methacrylatoethyl trimethyl ammonium chloride (DMC) with silk fabrics was carried out using ammonium persulfate (APS) initiator, for further endowing silk with antibacterial ability. The results from liquid chromatography-mass spectrometry (LC-MS), FTIR and Raman spectra verified the formation of the azo dyestuff from diazo salts and tyrosine model compound. The silk fabric exhibited high color depth and satisfactory color fastness after in situ coloring. For the fabric coupled with diazo salt of 4-vinylphenylamine (DVA), the introduced vinyl groups might further graft copolymerize with DMC, resulting in a noticeable antibacterial effect with the antibacterial ratio of 96.38%. Meanwhile, no strengthen loss was detected after the combination treatments. The combined use of in situ coloring and APS-initiated cascade antibacterial functionalization provides a novel and energy-saving approach for dyeing and functionalization of silk fabrics under mild treating conditions.